Towards computational models of animal cognition, an introduction for computer scientists - Ma, Zhanshan (Sam) (Cognitive systems research, 2015)
The last few years of the twentieth century witnessed the emerging convergence of biology and computer science and this trend has been accelerating since then. The study of animal behavior or behavior biology has been one of the major contributors for this convergence. Behavior is fascinating because it is the response of an organism to internal and external signals and it is controlled by complex interactions among nerves, the sensory and the motor systems. To some extent, behavior is similar to the output (or response) of a computer system or a network node if we consider an animal brain as a computer node. This paper is the first in a two-part series in which I review the state-of-the-art research in behavior biology inspired computing and communication, with the first part focusing on animal cognition and the second part on animal communication (Ma, 2014). The present article also assumes the task of presenting a general introduction on behavior biology literature, which sets a foundation for synthesizing both parts of the series but the synthesis will be performed in the second part of the series. I sets three objectives in this ‘cognition’ part: (i) to present a brief overview on the literature of behavior biology for computer scientists; (ii) to summarize the state-of-the-art studies in several cognitive aspects of animal behavior: focusing on emerging research in cognitive ecology, social learning and innovation, as well as animal logics; (iii) to review some important existing studies inspired by animal behavior and further present a perspective on the future research. These cognition-related topics offer insights for research fields such as machine learning, human computer interactions (HCI), brain computer interfaces (BCIs), evolutionary computing, pervasive computing, etc. In perspective, I suggest that the interaction between behavioral biology and computer science should be bidirectional, and a new subject, behavioral informatics, or more general computational behavior biology, should be developed by the cooperative efforts between biologists and computer scientists.